Evaluasi Pelaksanaan dan Perumusan Strategi Keberlanjutan Program Akuaponik untuk Kesejahteraan Masyarakat - Asep Taryana (Institut Pertanian Bogor, 2022)
Serving Lecturer activity is one of the community service programs organized by Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) IPB as an effort to develop and apply Science and Technology for the welfare of the community. This activity was held in Muncangela Village, Cipicung District, Kuningan Regency. The stages of this activity are socialization, counseling, mentoring, Focus Group Discussion (FGD), implementation of activities, and formulation of strategies for the sustainability of the akuaponiks program. Based on the research results, to realize the sustainability of these activities, there are strategic assumptions obtained from experts and analyzed by the SAST method. The assumptions are selected based on the level of importance and the level of certainty and are integrated into a strategy called